Immunogenomic profile at baseline predicts host susceptibility to clinical malaria - Mbambo, Gillian; Dwivedi, Ankit; Ifeonu, Olukemi O.; Munro, James B.; Shrestha, Biraj; Bromley, Robin E.; Hodges, Theresa; Adkins, Ricky S.; Kouriba, Bourema; Diarra, Issa; Niangaly, Amadou; Kone, Abdoulaye K.; et al. (Frontiers in Immunology, 2023)
Abstract Host gene and protein expression impact susceptibility to clinical malaria, but the balance of immune cell populations, cytokines and genes that contributes to protection, remains incompletely understood. To identify determinants of host susceptibility to clinical malaria at a time when acquired immunity is developing, we analyzed peripheral blood mononuclear cells (PBMCs) collected from children who differed in susceptibility to clinical malaria, all from a small town in Mali. PBMCs were collected from children aged 4-6 years at the start, peak and end of the malaria season. We characterized the immune cell composition and cytokine secretion for a subset of 20 children per timepoint (10 children with no symptomatic malaria age-matched to 10 children with >2 symptomatic malarial illnesses), and gene expression patterns for six children (three per cohort) per timepoint. We noted higher frequency of HLA-DR+ CD4 T cells in protected children during the peak of the malaria season and comparable levels cytokine secretion after stimulation with malaria schizonts across all three time points. We also observed differences between the two groups of children in the expression of genes related to cell death and inflammation; in particular, inflammatory genes such as CXCL10 and STAT1 and apoptotic genes such as XAF1 were upregulated in susceptible children before the transmission season began. This suggests that differences in apoptotic and inflammatory gene expression patterns can predict susceptibility to clinical malaria.